Source-it : global material sourcing for the clothing industry (ITC GenevaCH, 2005)
Deals with the dynamics of the global textiles and clothing supply chain, also with why and how garment manufacturers need to develop alternative sourcing and supply management approaches.
Keywords: CLOTHING INDUSTRY